METODOLOGÍA PARA EL DESARROLLO DE LA VELOCIDAD DE REACCIÓN EN NIÑOS FUTBOLISTAS DE LA CATEGORÍA SUB 12 DE LA LIGA DEPORTIVA CANTONAL DE VINCES PROVINCIA DE LOS RÍOS - MORÁN VERGARA JORGE WILSON (2024)
“Methodology for the development of reaction speed in child soccer players of the under 12 category of the cantonal sports league of Vinces, province of Los Ríos” reveals the current situation presented by the soccer coaches of the aforementioned institution, to fulfill the objectives. planned, methods were selected from the theoretical and empirical levels of scientific research, where mathematical and statistical methods were used whose purpose was to process and validate the results obtained. The shortcomings observed in the visits made to ten training sessions served as a basis for determining the elements that should contain a model to support the training system for the development of reaction speed in child soccer players in the under 12 category. the cantonal sports league of Vinces province of Los Ríos, which is in the Under 12 category. It was thought that the use of the proposed elements, as a basis for the development of the aforementioned model, can contribute to raising the scientific level of the coaches to face the pedagogical direction of the training process aimed at the development of the physical capabilities of its athletes.